Pharmacogenetic Associations Between Atazanavir/UGT1A1*28 and Efavirenz/rs3745274 (CYP2B6) Account for Specific Adverse Reactions in Chilean Patients Undergoing Antiretroviral Therapy - Poblete, Daniela; Bernal, Fernando; Llull, Gabriel; Archiles, Sebastian; Vasquez, Patricia; Chanqueo, Leonardo; Soto, Nicole; Lavanderos, María A.; Quiñones, Luis A.; Varela, Nelson M. (Frontiers in Pharmacology, 2021)
Background. Efavirenz (EFV), a non-nucleoside reverse transcriptase inhibitor, and atazanavir (ATV), a protease inhibitor, are drugs widely used in antiretroviral treatment (ART) for people living with HIV. These drugs have shown high interindividual variability in adverse drug reactions (ADRs). UGT1A1*28 and CYP2B6 c.516G>T have been proposed to be related with higher toxicity by ATV and EFV, respectively. Objective. To study the association between genetic polymorphisms and ADRs related to EFV or ATV in patients living with HIV treated at a public hospital in Chile. Methods. Epidemiologic, case-control, retrospective and observational study in 67 adult patients under EFV or ATV treatment, in the San Juan de Dios Hospital. Data were obtained from patient`s medical records. Genotype analyses were performed using rtPCR for rs887829 (indirect identification of UGT1A1*28 allele) and rs3745274 (CYP2B6 c.516G>T), with TaqMan® probes. The association analyses were performed with univariate logistic regression between genetic variants using three inheritance models (codominant, recessive and dominant). Results. In ATV-treated patients hyperbilirubinemia (total bilirubin >1.2 mg/dL) had the main incidence (61.11%), and moderate and severe hyperbilirubinemia (total bilirubin >1.9 mg/dL) was statistically associated with UGT1A1*28 in recessive and codominant inheritance models (OR=16.33, p=0.028 and OR=10.82, p=0.036, respectively). On the other hand, in EFV treated-patients adverse reactions associated with CNS toxicity reached 34.21%. In this respect, nightmares showed significant association with CYP2B6 c.516G>T, in codominant and recessive inheritance models (OR=12.00, p=0.031 and OR=7.14, p=0.042, respectively). Grouped CNS ADRs (nightmares, insomnia, anxiety and suicide attempt), also showed a statistically significant association with CYP2B6 c.516G>T in the codominant and recessive models (OR=30.00, p=0.011 and OR=14.99, p=0.021, respectively). Conclusion. Our findings suggest that, after treatment with ATV or EFV, UGT1A1*28 and CYP2B6 c.516G>T influence the appearance of moderate to severe hyperbilirubinemia and CNS toxicity, respectively. However, larger prospective studies will be necessary to validate these associations in our population. Without a doubt, improving adherence in patients living with HIV is a critical issue to the success of therapy. Hence, validating and applying international pharmacogenetics recommendations in Latin American countries would improve the precision of ART, a fundamental aspect to achieve the 95-95-95 treatment target proposed by UNAIDS.